Effect of different postures and loads on joint motion and muscle activity in older adults during overhead retrieval - Zhou, Chengmin; Xu, Xue; Huang, Ting; Kaner, Jake (Frontiers in Physiology, 2024)
Pain is a common health problem among older adults worldwide. Older adults tend to suffer from arm, lumbar, and back pain when using hanging cabinets. This study used surface electromyography (EMG) to record muscle activity and a motion capture system to record joint motion to research effects of different loads and retrieval postures on muscle activity and joint range of motion when older adults retrieve objects from a high place, to provide optimised feedback for the design of hanging cabinet furniture. We found that: (1) The activity of BB (Biceps brachii) on the side of the body interacting with the cabinet door was greater than that of UT (Upper trapezius) and BR (Brachial radius) when retrieving objects from a high place, the activity of UT on the side of the body interacting with a heavy object was greater than that of BB and BR. (2) The activity of UT decreases when the shoulder joint angle is greater than 90°, but the activity of BB increases as the angle increases. In contrast, increasing the object's mass causes the maximum load on the shoulder joint. (3) Among the different postures for overhead retrieval, alternating between the right and left hand is preferable for the overhead retrieval task. (4) Age had the most significant effect on overhead retrieval, followed by height (of person), and load changes were significantly different only at the experiment's left elbow joint and the L.BR. ( 5) Older adults took longer and exerted more effort to complete the task than younger adults, and static exercise in older adults may be more demanding on muscle activity in old age than powered exercise. These results help to optimise the design of hanging cabinet furniture. Regarding the height of hanging cabinets, 180 cm or less is required for regular retrieval movements if the human height is less than 150 cm. Concerning the depth of the hanging cabinets, different heights chose different comfort distances, which translated into the depth of the hanging cabinets; the greater the height, the greater the depth of the hanging cabinets to use.